2007
DOI: 10.1099/mic.0.2006/003608-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane topology and mutational analysis of the osmotically activated BetT choline transporter of Escherichia coli

Abstract: For osmoprotection, Escherichia coli can synthesize glycine betaine from externally supplied choline by the Bet system (betTIBA products). The major carrier of choline is the high-affinity, proton-driven, secondary transporter BetT, which belongs to the BCCT family of transporters. Fusion proteins consisting of N-terminal fragments of BetT linked to b-galactosidase (LacZ) or alkaline phosphatase (PhoA) were constructed. By analysis of 51 fusion proteins with 37 unique fusion-points, the predictions that BetT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Previously, we showed that choline uptake by P. syringae BetT, which is 53% and 79% identical to BetT1 and BetT3, respectively, increases with increasing osmolarity and that both osmoregulation and activity in high-salt environments depend on the presence of a C-terminal tail (6). Domain analysis of E. coli BetT also demonstrated the importance of the C-terminal tail for the osmoregulation of transport activity (37). The fact that BetT3 is salt activated (5) but BetT1 is not (data not shown) may be due to the fact that BetT1 lacks the cytoplasmic C-terminal tail, which follows the 12th transmembrane helix in P. syringae BetT and P. aeruginosa BetT3.…”
Section: Discussionmentioning
confidence: 79%
“…Previously, we showed that choline uptake by P. syringae BetT, which is 53% and 79% identical to BetT1 and BetT3, respectively, increases with increasing osmolarity and that both osmoregulation and activity in high-salt environments depend on the presence of a C-terminal tail (6). Domain analysis of E. coli BetT also demonstrated the importance of the C-terminal tail for the osmoregulation of transport activity (37). The fact that BetT3 is salt activated (5) but BetT1 is not (data not shown) may be due to the fact that BetT1 lacks the cytoplasmic C-terminal tail, which follows the 12th transmembrane helix in P. syringae BetT and P. aeruginosa BetT3.…”
Section: Discussionmentioning
confidence: 79%
“…Although the measured differences are small, they are systematically seen for all pH values tested. The role of betaine as an osmoprotectant for E. coli under osmotic stress is well described (Culham et al 2001;Ly et al 2004;Tøndervik and Strøm 2007), but the exact mechanism for its protective role under pH stress is unknown. Nevertheless, there are indications of overlapping mechanisms and roles for osmolytes in osmotic and pH homeostasis (Kitko et al 2010;Wang et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For intracellular synthesis of glycine betaine, the precursor choline is imported via the osmosensing transporter betT of the betaine-camitine-choline transporter 115, 184, 204 41, 203 5, 15, 71, 89, 159, 203 42, 100, 122, 150 44, 118, 126 63, 74, 90, 91, 163, 204 8, 55, 84, 104, 105, 191 23, 45, 87, 181, 187 32, 149 37, 86, 95, ¡01, 102, 170 70, 76, 131, 147, 166-168, 174, 192, 194 family and is converted to glycine betaine aldehyde by the choline dehydrogenase BetA followed by a second dehydrogenation by BetA or the betaine aldehyde dehydrogenase BetB (8,105,191). The expression of the bet genes is induced by osmotic stress and the presence of choline and oxygen (55,105).…”
Section: Osmotic Stress Response Mechanisms In E Colimentioning
confidence: 99%